The Existence Of Islamic Education In Pandemic Times: (Case Study on Communities Not Having Online Learning Facilities) - Abdul Hopid; Hanif Cahyo Adi Kistoro (Fikroh: Jurnal Pemikiran dan Pendidikan Islam, 2022)
The existence of islamic education in pandemic times (case study on communities not having online learning facilities). the covid-19 pandemic has had a significant impact on the world of education, including Islamic education. The limited facilities owned by students also affect the learning model. This study examines the factors that encourage and become essential reasons for the ongoing face-to-face learning process and the impacts of the pandemic. This research is field research with qualitative research methods. Participants in this study amounted to 12 people consisting of teachers, principals, guardians of students, and students. Data were collected through observation, interviews, and open questionnaires. After a thorough interpretation, the collected data was analyzed by classifying, reducing, and then summing up. The study results found that three factors drove the continued existence of Islamic education in the first community because online learning policies were considered to cause problems for parents, schools, and teachers. Second, the public's understanding of COVID-19 is not very dangerous, so it is deemed to be regular. Some schools continue to carry out face-to-face learning adjusted to government policies. Third, there is support and agreement from the school, community leaders, and parents so that face-to-face learning can run as usual, even though the time is minimal.